Depression severity and verbal comprehension in children and adolescents with a major depressive episode - Monia Trasolini; Giulia Serra; Maria Elena Iannoni; Elisa Andracchio; Massimo Apicella; Massimo Apicella; Gino Maglio; Deny Menghini; Stefano Vicari; Stefano Vicari (Frontiers in Psychiatry)
IntroductionSevere depression is a prevalent psychiatric illness in children and adolescents associated with high levels of morbidity, disability, and a high risk of suicidal behavior. Cognitive factors associated with depression severity in juveniles have been poorly reported. MethodsWe investigated the relationship between depression severity and intelligence quotient (IQ)with its subscales in 65 juveniles (aged 10–17 years) with a current major depressive episode evaluated at the Mood Disorder Program of Bambino Gesù Children’s Hospital in Rome. Pearson’s correlation analyses were followed by a Benjamini–Hochberg correction and linear multivariable regression model. ResultsDepression severity measured with the total score of the Children’s Depression Rating Scale-Revised (CDRS-R) was positively associated with the Verbal Comprehension Index (VCI; Pearson’s r = 0.309 [0.042−0.534]; p = 0.024). The CDRS-R subscales positively associated with VCI by Pearson’s correlation were depressed feelings, suicidal ideation, excessive weeping, and reduced facial expressions. Suicidal ideation was the only factor independently and significantly associated with higher VCI in the multivariable linear regression model.DiscussionSuicidal ideation was significantly and independently associated with higher verbal comprehension, indicating that depressed juveniles with better verbal ability may be at a greater risk of showing suicidal ideation.